PERENCANAAN PEMBELAJARAN DALAM PENDIDIKAN ANAK USIA DINI - Eka Saptaning Pratiwi; Ahmad Farid Utsman (Abata : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This study aims to explain (1) Teacher Preparation in Early Childhood classroom, (2) Problems in Early Childhood Classroom preparation. This qualitative research uses a case study approach. The data source was obtained by interviewing some preschool teachers who was studying at STIT Muhammadiyah Bojonegoro. This study used a qualitative research approach. Qualitative Research was a type of research which didn’t apply statistics procedure or any other quantitative procedure. Qualitative research is a research approach which tends to let the researcher to understand social phenomenon from the perspective of participant. The results obtained are as follows Early childhood education teachers prepared learning started from the beginning of the semester by preparing semester programs, learning topics, learning resources to daily implementation plans. The problems faced in preparing for learning in early childhood are conditional problems caused by the very diverse characteristics of early childhood.